AAC 26-15 soybean - K. Yu; L. Woodrow; V. Poysa (Canadian Journal of Plant Science, 2015)
Yu, K., Woodrow, L. and Poysa, V. 2015. AAC 26-15 soybean. Can. J. Plant Sci. 95: 441–443. AAC 26-15 is a high-yielding, high-protein, SCN resistant, food grade soybean cultivar with yellow hila and acceptable processing quality for foreign and domestic tofu and soymilk markets. It was developed at Agriculture and Agri-Food Canada (AAFC), Greenhouse and Processing Crops Research Centre (GPCRC), Harrow, Ontario. AAC 26-15 is adapted to areas of southwest Ontario with 3100 or more crop heat units and has a relative maturity of 2.3 (MG 2.3).